2008
DOI: 10.1152/ajpheart.01285.2007
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of cells obtained from human cord blood CD34+ stem cells and mouse cardiac myocytes in coculture

Abstract: Prior in vitro studies suggested that different types of hematopoietic stem cells may differentiate into cardiomyocytes. The present work examined whether human CD34+ cells from the human umbilical cord blood (hUCB), cocultured with neonatal mouse cardiomyocytes, acquire the functional properties of myocardial cells and express human cardiac genes. hUCB CD34+ cells were cocultured onto cardiomyocytes following an infection with a lentivirus-encoding enhanced green fluorescent protein (EGFP). After 7 days, mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 52 publications
5
14
0
Order By: Relevance
“…Neonatal cardiomyocytes were isolated from 1-2-day-old SWISS CD1 mice as described previously (40) and specified in the supplemental "Experimental Procedures." To minimize the number of residual proliferating cardiomyocytes and of contaminating fibroblasts, cell cultures were cultured in minimal essential medium containing 10% FBS in the presence 20 M cytosine ␤-D-arabinofuranoside (AraC, C1768 Sigma) for 48 h. After a 3-day recovery time in AraC-free medium, neonatal cardiomyocytes were transfected.…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal cardiomyocytes were isolated from 1-2-day-old SWISS CD1 mice as described previously (40) and specified in the supplemental "Experimental Procedures." To minimize the number of residual proliferating cardiomyocytes and of contaminating fibroblasts, cell cultures were cultured in minimal essential medium containing 10% FBS in the presence 20 M cytosine ␤-D-arabinofuranoside (AraC, C1768 Sigma) for 48 h. After a 3-day recovery time in AraC-free medium, neonatal cardiomyocytes were transfected.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work (36), we showed that human cord blood CD34 ϩ cells, when cocultured on neonatal mouse cardiomyocytes, exhibit excitation-contraction coupling features similar to those of cardiomyocytes, even though no human genes were upregulated. The aims of the present work are to investigate whether human CD34 ϩ cells, isolated after 1 wk of coculture with neonatal ventricular myocytes, possess molecular and functional properties of cardiomyocytes and to discriminate, using a reporter gene system, whether cardiac differentiation derives from a (trans)differentiation or a cell fusion process.…”
mentioning
confidence: 85%
“…ϩ UCB cells in coculture with mouse neonatal cardiomyocytes functionally integrate within the substrate, no data about the time course of this integration were previously described (36) (Fig. 1A), while the EGFP ϩ / CD34 ϩ cells did not contract and were electrically inactive and depolarized ( Fig.…”
Section: Electrophysiological Features Of Cd34mentioning
confidence: 96%
See 2 more Smart Citations